Evaluation of Children with Attention Deficit Hyperactivity Disorder on the Wechsler Intelligence Scale for Children-IV - Berkan Şahin; Miraç Barış Usta; Bedia Sultan Önal; Esra Hoşoğlu (Çocuk Dergisi)
Objective: The aim of this study was to evaluate the cognitive performance and clinical characteristics of children and adolescents with Attention Deficit Hyperactivity Disorder (ADHD) who had attended a tertiary center. Method: Fifty-six children and adolescents aged 7-16 years with ADHD who had been admitted to the Child and Adolescent Psychiatry clinic between June 2020 and March 2021 were retrospectively included in the study. A semi-structured interview form for the Affective Disorders and Schizophrenia Interview Schedule-Present Version for School-Age Children was used to determine mental disorders. The Clinical Global Impression Scale (CGIS) was completed to assess the severity of ADHD symptoms. The Wechsler Intelligence Scale for Children-IV (WISC-IV) was used in the assessment of cognitive skills. Results: The median age of the participants was 13 and 71.4% of them were male. The Working memory index (s=83.3) and Full-Scale IQ (FSIQ) (s=84) were found to be the lowest scores. According to the comparisons between CGIS, the FSIQ score (χ2 =0.736; p=0.947), verbal comprehension index (χ2 =2.882; p=0.578), perceptual reasoning index (χ2 =1.412; p=0.842), working memory index (χ2 =1.980; p=0.739), processing speed index (χ2 =1.673; p=0.796) were not found to be statistically different between the groups. Conclusion: The WISC-IV scale, which is increasingly preferred in the clinic use, could help to obtain information about cognitive performance in children with ADHD, regardless of the severity of ADHD symptoms.